“incorporación de materiales autoinstructivos digitales de calidad, como estrategia didáctica para fortalecer el proceso de enseñanza aprendizaje en la universidad nacional de San Martín – Tarapoto” - Barzola Cárdenas, Abner Milán (2015)
This experimental work was performed to measure to what degree will strengthen the incorporation of digital self-instructíonal materials in teaching-learning process, in Professional Academic 5choo1 of Agro-industrial Engineering in the National University of San Martin-Tarapoto, using as a sample two groups of 27 and 17 student's; and as instruments: The Training mixed mode, Syllabus and digital self instruction manual; and also the Test for evaluating and improving the teaching learning process. The results confirm the research hypothesis since it has been shown that the incorporation of Digital Quality Auto-instructiva Materials significantly strengthened the teaching-learning process at the National University of San Martín-Tara.poto, 'Since executing statistical tests, it was observad that the average the post test experimental group significantly exceeded to the post test control group, with a Te= 11,37 plus to right Tabular= 1.682, being a= 0.05.